The effect of pelvic osteotomy plate type on axial rotation of the acetabular segment in the triple pelvic osteotomy - Clark, B.; Wallace, L. J.; Pacchiana, P. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
Objective: The purpose of this study is to evaluate the changes in structural anatomy of cadaver pelves, with specific emphasis on axial rotation, resulting from the application of TPO plates differing by type, angle and orientation. Sample population: Nine cadaver pelves procedure: The degree of axial rotation was determined for three different pelvic osteotomy plate types, four different plate angles and two different orientations of the same plate. Results: The observed degree of axial rotation was significantly different than the degree of axial rotation predicted by the plate angle for each group except the Rooks pelvic osteotomy plate. Conclusions/ clinical relevance: In the triple pelvic osteotomy the final degree of axial rotation may be significantly different than the predetermined plate angle.
Keywords: Triple pelvic osteotomy; plate angle; axial rotation; acetabular segment; plate position